Conformable Impulsive Delay Differential Equations - Sunkavilli, Madhuri; Deekshitulu, G.V.S.R. (Journal of Applied Nonlinear Dynamics, 2026)
This paper studies the conformable delay differential systems with linear impulses. Firstly, with the help of impulsive delayed exponential matrix function of conformable version and the variation of constants method, we obtain a representation of solutions to homogeneous and non-homogeneous differential equations. Secondly, the existence and uniqueness of solutions to nonlinear conformable impulsive delay differential equations are proved by using Schaefer’s fixed-point theorem and Banach fixed-point principle. Finally, an example is given to illustrate our theoretical results.